Ceramics - De Waal, Edmund (London New Holland, 2003)
From handmade tiles to domestic tileware and one-off sculptural pieces in earthenware, stoneware and porcelain, this exciting book represents the best in contemporary design from all over the world
Include Color Illustration and Index
Keywords: Pottery -- Design -- Pottery